2024
DOI: 10.3390/bs14020142
|View full text |Cite
|
Sign up to set email alerts
|

“We Need to Raise Awareness and Never Give Up”: Israeli Druze and Muslim Arab Kindergarten Teachers’ Proactivity When Facing the Sexual Abuse of Their Students

Noah Bar Gosen,
Laura I. Sigad,
Jordan Shaibe
et al.

Abstract: Kindergarten teachers are expected to lead the intervention process in cases of child sexual abuse (CSA) in their kindergarten. This study examines the proactive role of Druze and Muslim Arab kindergarten teachers in addressing and coping with the CSA of their kindergarten students in Israel. A qualitative thematic analysis was used to investigate the semi-structured interviews conducted with eight Druze Arab and six Muslim Arab kindergarten teachers. Three distinct themes were revealed. The first theme descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Despite a gradual societal shift towards acknowledging CSA's gravity and the importance of sex education [88,89], integrating these elements into their professional identity poses a substantial cultural challenge. Thus, consistent with prior research among Arab educators in Israel [13,46,50], Arab school counselors strive to strike a balance between acting as agents of social change and adhering to their cultural sensitivities. Yet, in instances where compromise is unattainable, they adopt a more proactive stance, positioning themselves as pivotal community figures driving change.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Despite a gradual societal shift towards acknowledging CSA's gravity and the importance of sex education [88,89], integrating these elements into their professional identity poses a substantial cultural challenge. Thus, consistent with prior research among Arab educators in Israel [13,46,50], Arab school counselors strive to strike a balance between acting as agents of social change and adhering to their cultural sensitivities. Yet, in instances where compromise is unattainable, they adopt a more proactive stance, positioning themselves as pivotal community figures driving change.…”
Section: Discussionmentioning
confidence: 57%
“…In Israel, differences between cultural subgroups significantly affect communities' interventions in cases of CSA (e.g., [46,[49][50][51]). Among the Israeli Jewish population, which constitutes approximately 74% of the total population, families often align with Western norms, featuring democratic relations and permissive parenting [48].…”
Section: School Counselors' Coping When Addressing Csa In Israelmentioning
confidence: 99%
See 1 more Smart Citation
“…Central to the perception of risks at a destination are those cultural and socioeconomic characteristics that revolve around religious values and customs [23]. Along this line, various cross-cultural studies have found that common cultural values may raise common fears and other emotions, thereby deterring tourists from traveling to some destinations [23]. Some studies have found differences in risk perceptions across individuals with different religious beliefs, i.e., Catholics, Protestants and Jews [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, some principals have been found to take an active leadership role, while others take a passive avoidance approach [38], and some act in solitude, while others share the responsibility with colleagues [30]. Among teachers, perceptions of their power, control, responsibility, and ability to act in regard to CSA cases have been found to diverge based on contextual factors, such as religion and socio-cultural and socio-political positions [7,39]. Previous positive or negative experiences may also deter or encourage educators to report suspected abuse [40].…”
Section: Responses Of Educators To Csa Survivors' Help-seeking Behaviorsmentioning
confidence: 99%